2006
DOI: 10.5194/angeo-24-153-2006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observation of sporadic E with a rapid-run ionosonde and VHF coherent backscatter radar

Abstract: Abstract. During the SEEK 2 rocket campaign, ionograms were recorded every minute at the Yamagawa Radio Observatory at about 90 km west of the region monitored by a VHF (very high frequency) coherent backscatter radar. Sporadic E-layer parameters, which include the critical (foEs) and blanketing (fbEs) frequencies, the layer height (h Es), and the width of the range spread of sporadic E-traces, were compared with RTI (range-time-intensity) plots of VHF quasiperiodic (QP) and continuous coherent backscatter ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 18 publications
9
63
0
2
Order By: Relevance
“…This is different from the postulated situation in the preceding E-F region coupling models, where both regions are perturbed at the same wave length Cosgrove and Tsunoda, 2004). The E s layer is known to be very inhomogeneous when QP echoes are observed (Ogawa et al, 2002;Maruyama et al, 2006). In our experiment, for example, when well-defined QP echoes were observed on 2 June 2006, the lowest electron density of the E s layer over the MU radar site was 6.0×10 10 m −3 (f b E s =2.2 MHz) which was less than 1/20 of the highest (1.4×10 12 m −3 , f o E s =10.5 MHz).…”
Section: Coupling Processes Between the E-and F Regionmentioning
confidence: 42%
See 2 more Smart Citations
“…This is different from the postulated situation in the preceding E-F region coupling models, where both regions are perturbed at the same wave length Cosgrove and Tsunoda, 2004). The E s layer is known to be very inhomogeneous when QP echoes are observed (Ogawa et al, 2002;Maruyama et al, 2006). In our experiment, for example, when well-defined QP echoes were observed on 2 June 2006, the lowest electron density of the E s layer over the MU radar site was 6.0×10 10 m −3 (f b E s =2.2 MHz) which was less than 1/20 of the highest (1.4×10 12 m −3 , f o E s =10.5 MHz).…”
Section: Coupling Processes Between the E-and F Regionmentioning
confidence: 42%
“…The ionosonde at the MU radar site, however, observed the strong and inhomogeneous E s layer 02:30-04:30 JST on 31 May 2005. f o E s and f b E s over the MU radar, which, respectively, correspond to the highest and lowest plasma density in E s layers, were 8.5 MHz (9×10 11 m −3 ) and 2 MHz (5×10 10 m −3 ). QP echoes are known to be closely related to large f o E s −f b E s (Ogawa et al, 2002;Maruyama et al, 2006). In fact, we find a few faint striations of E region echoes in this time period.…”
Section: Coincidence Of Qp Echoes and Mstidsmentioning
confidence: 59%
See 1 more Smart Citation
“…Accumulation of the E-region plasma into the layers is well explained by the shear of the neutral wind (Bernhardt et al, 2005;Larsen et al, 2005;Pfaff et al, 2005;Wakabayashi and Ono, 2005;Yokoyama et al, 2005). The Es-layers are spatially modulated by the motion of the neutral atmosphere (Maruyama et al, 2006), and then FAI echoes start to appear. The sources of the FAIs are the plasma-density gradient of Published by Copernicus GmbH on behalf of the European Geosciences Union.…”
mentioning
confidence: 99%
“…Our observation that the E S layer echo intensity in different range bins is modulated by 5 to 20 min quasi periods both during day time and night time, and the QP echoes at 150 km are also observed during day time in low latitudes (Patra and Rao, 2006) is to be investigated in terms of the gravity wave modulation of the irregularities during different times of the day. Maruyama et al (2006) found a close relationship between the appearance of QP echoes in the RTI plot and the level of in-homogeneity in Sporadic E plasma, signified by the difference between f b E S and f o E S . During QP echo events, f o E S increased while f b E S decreased so that the difference between these two enhanced indicating the development of strong spatial structuring in electron density within the sporadic E layer.…”
Section: Summary and Discussionmentioning
confidence: 91%